Senegal : Second Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria-Staff Report; Informational Annex; Press Release. (IMF Staff Country Reports; Country Report, 2011)
The Second Review under the policy support instrument (PSI) highlights that Senegal's economy has remained resilient to the global economic turmoil. In line with the authorities' new Document of Economic and Social Policies for 2011-15, the 2012 economic program supported under the PSI will target critical bottlenecks in energy and infrastructure, which hinder growth and poverty reduction. The fiscal program will allow the authorities to scale up infrastructure investment, but requires keeping a prudent stance on the rest of the budget.